2017
DOI: 10.1016/j.chroma.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Size exclusion chromatography with superficially porous particles

Abstract: A comparison is made using size-exclusion chromatography (SEC) of synthetic polymers between fully porous particles (FPPs) and superficially porous particles (SPPs) with similar particle diameters, pore sizes and equal flow rates. Polystyrene molecular weight standards with a mobile phase of tetrahydrofuran are utilized for all measurements conducted with standard HPLC equipment. Although it is traditionally thought that larger pore volume is thermodynamically advantageous in SEC for better separations, SPPs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…However, recent studies have shown the potential of fast SEC, using UHPLC technology . More recently, the use of core–shell particles in 2 D SEC to improve resolution was demonstrated and this was later confirmed . SEC is an intrinsically isocratic separation.…”
Section: Selection and Combination Of Selectivitiesmentioning
confidence: 99%
“…However, recent studies have shown the potential of fast SEC, using UHPLC technology . More recently, the use of core–shell particles in 2 D SEC to improve resolution was demonstrated and this was later confirmed . SEC is an intrinsically isocratic separation.…”
Section: Selection and Combination Of Selectivitiesmentioning
confidence: 99%
“…As anticipated for SEC, the elution order is from largest solute to the smallest solute. A detailed experimental comparison of SEC between FPPs and SPPs has been conducted [24] and shows that SEC with SPPs offers advantages in speed, efficiency and plate production per unit time. The range of molecular weights used in Figure 12 spans the radius of gyration range [24] of 43 Å to 662 Å showing that the lowest MW standard of 17.5 kDa will fit into the smallest pore material in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed experimental comparison of SEC between FPPs and SPPs has been conducted [24] and shows that SEC with SPPs offers advantages in speed, efficiency and plate production per unit time. The range of molecular weights used in Figure 12 spans the radius of gyration range [24] of 43 Å to 662 Å showing that the lowest MW standard of 17.5 kDa will fit into the smallest pore material in Figure 12. The largest MW standard is excluded by both pore systems with the caveat that the pore size distribution shown in Figure 3 demonstrates that a limited number of pores exist larger than 1000 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The total pore volume is reduced for the core-shell particles, and hence a lower loading capacity, when compared to [174] the standard SEC porous particles. But this is usually compensated for by an increase in efficiency.…”
Section: Core-shell Particle Columns For Secmentioning
confidence: 99%